MODERN FEATURES OF HR TRANSFORMATIONAL CHANGES AND MARKETING COMMUNICATIONS IN NON-GOVERNMENTAL ORGANIZATIONS - Іванченко, Галина; Бондарчук, Людмила; Семенюк, Ірина; Веслова, Яна (SWorldJournal, 2025)
This article examines the implementation of modern human resource management (HRM) approaches in the operations of civil society organizations (CSOs) and highlights the need for a comprehensive rethinking of personnel practices and the development of an